Global index of the acoustic climate - Piechowicz, J. (Archives of Acoustics, 2004)
The paper deals with the essential problem of noise protection in the work environment. It develops the criteria of the assessment of the acoustic climate quality in industrial rooms, often already at the stage of their designing. The requirements of the acoustic safety of workplaces force to improve constantly the processing of the results of model and experimental investigations and to search for synthetic ways of presentation of the acoustic quality of industrial rooms in order to be able to estimate the risk of occupational diseases for the employees exposed to noise. Until quite lately, the index method of assessment of the acoustic climate of industrial rooms was based - on three partial indices: the technological one, the sound power and the acoustic properties of the room. The paper presented here expands the method by introducing additional indices: the index of impulse and impact noise, the index of fittings density of the room, the index of the noise spectrum distribution and the index of low-frequency noise. Such broad formulation of acoustic phenomena in industrial rooms by the single-numbered Global Index is an innovatory enterprise. The indices were experimentally estimated in the Forge.